1991
DOI: 10.1159/000282207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trospium Chloride on Urodynamic Parameters in Patients with Detrusor Hyperreflexia due to Spinal Cord Injuries

Abstract: In a multicentre placebo-controlled double-blind study 61 patients with spinal cord injuries and detrusor hyperreflexia were treated: 20 mg trospium chloride was given twice daily over a period of 3 weeks. Pre- and posttreatment urodynamic measurements demonstrated large improvements in maximum cystometric capacity (mean = 138.1 ml), decreased maximum detrusor pressure (mean = ––37.8 cm H2O) and an increase in compliance (mean =12.1 ml/cm H2O) in the treatment group. Urodynamic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 5 publications
4
40
0
1
Order By: Relevance
“…12 Placebo-controlled studies. The study characteristics of the five placebo-controlled proof of efficacy studies with oxybutynin IR, 13 propiverine IR, 14 trospium chloride IR, 15 tolterodine IR 16 and solifenacin 17 are summarized in Table 1b.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Placebo-controlled studies. The study characteristics of the five placebo-controlled proof of efficacy studies with oxybutynin IR, 13 propiverine IR, 14 trospium chloride IR, 15 tolterodine IR 16 and solifenacin 17 are summarized in Table 1b.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The results with respect to the key efficacy outcome parameters, maximum detrusor pressure and maximum cystometric bladder capacity, are summarized in Tables 2a and 2b: Comparing AM with placebo resulted in significant differences with negligible effects of placebo. [13][14][15] Unequivocally, placeboand active-controlled studies with reported urodynamic outcomes demonstrated a significant decrease of B30-40% in maximum detrusor pressure, paralleled by a significant increase of maximum cystometric bladder capacity of B30-40% for oxybutynin IR, propiverine IR, propiverine ER and trospium chloride IR. [13][14][15][19][20][21] The effects of solifenacin 10 mg were distinctly less pronounced.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are ineffective in some patients and are often associated with bothering side effects such as dry mouth, constipation and blurred vision. 2,4 The clinical and urodynamic efficacy of anticholinergic agents in SCI patients has been evaluated in a limited number of studies. [5][6][7][8][9] They all showed a significant decrease in the number of leakages per day with improved quality of life.…”
mentioning
confidence: 99%
“…Trospium chloride, a mixed antimuscarinic agent and a smooth muscle relaxant, is also a potential drug for neurogenic bladder management as it was shown to improve cystometric capacity and reduce incontinence episodes. 15 These drugs are well tolerated and safe, even during long-term treatment. They have diverse tolerance profiles so that a different antimuscarinic agent may be prescribed if a patient experiences adverse effects or if the therapeutic effect is not sufficient.…”
Section: Antimuscarinic Receptor Antagonistmentioning
confidence: 99%